1998
DOI: 10.1002/(sici)1097-0185(199801)250:1<80::aid-ar8>3.0.co;2-i
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative light microscopic study on the heterogeneity in the superficial pineal gland of the rat

Abstract: Background: The previous results regarding regional and day-night differences in pinealocyte size in rats are conflicting. The relationships between these differences and the vascularity and sympathetic innervation have scarcely been investigated. Methods: Wistar-King rats, kept under light/dark 12:12, were killed at midday or midnight in October. The nuclear density of pinealocytes in the superficial pineal was measured on the dorsoperipheral, dorsocentral, ventroperipheral, and ventrocentral regions at dista… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 38 publications
(51 reference statements)
2
6
0
Order By: Relevance
“…antigen and it was suggested that the more strongly stained cells, being concentrated distally, were under sympathetic control. A similar gradient change was also found in terms of the pinealocyte size, area of blood vessels and length of tyrosine hydroxylase (TH) 5 fibers that were larger toward the distal level [23]. All the above-mentioned findings suggest a regional heterogeneity and differential gradient of pineal elements.…”
Section: Discussionsupporting
confidence: 62%
See 4 more Smart Citations
“…antigen and it was suggested that the more strongly stained cells, being concentrated distally, were under sympathetic control. A similar gradient change was also found in terms of the pinealocyte size, area of blood vessels and length of tyrosine hydroxylase (TH) 5 fibers that were larger toward the distal level [23]. All the above-mentioned findings suggest a regional heterogeneity and differential gradient of pineal elements.…”
Section: Discussionsupporting
confidence: 62%
“…Previous study further showed that norepinephrine was the potent inhibitor of MHC class II expression on isolated microglia after IFN‐gamma stimulation [29]. In this regard, the sparse distribution of MHC class II positive PMM in the distal portion of the pineal gland may be attributed to a richer sympathetic innervation in the same area [23].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations